Polycentric Governance in Collective Action in the Implementation of Affirmative Policy to Improve the Economy of OAP in Sorong City: JEL Classification: H77, H83, J15, O17 - Tamrin Tajuddin; Sukri Sukri; Muh. Akmal Ibrahim; Didik Iskandar (Journal of Management and Administration Provision, 2026)
The implementation of economic affirmative action policies for Indigenous Papuans (OAP) in Sorong City operates within a polycentric governance landscape involving multiple centers of authority with different levels of legitimacy and capacity. This study examines how polycentric governance dynamics influence the effectiveness of affirmative action policies by applying a Polycentric Governance framework consisting of eight analytical dimensions: diversity of authority centers, institutional autonomy, cross-scale coordination, legitimacy of customary governance, institutional adaptability, democratic participation, integration of local knowledge, and sustainability outcomes. A descriptive qualitative approach was employed involving 45 policy actors and 158 Indigenous Papuan business actors through in-depth interviews, participant observation, and document analysis. The findings reveal that although 12 centers of authority are involved in policy implementation, cross-scale coordination reaches only 23.4% effectiveness due to the absence of institutional mechanisms integrating formal government authority with the customary Moi governance system. Customary institutions possess strong social legitimacy, with 87% of Indigenous Papuans recognizing their authority, yet their participation in policy formulation remains limited at only 12%. This disconnect contributes to overlapping authority in 34% of programs and unmet economic empowerment needs in 41% of cases. The study concludes that polycentricity without coordination mechanisms and recognition of plural legitimacy leads to institutional fragmentation rather than adaptive governance. It proposes prerequisites for productive polycentric governance, including clear authority boundaries, mutual recognition, and bridging institutional forums.